Method for improving dielectric constant uniformity of high dielectric constant filler modified anti-pollution flashover coating

By using activated group-modified silicon oxide particles and high dielectric constant fillers in the anti-fouling flash coating for chemical bonding, a dielectric gradient structure is formed that gradually decreases, which solves the problem of uneven electric field distribution caused by high dielectric constant fillers, and improves the electrical performance and durability of the coating.

CN119505695AActive Publication Date: 2025-02-25ELECTRIC POWER RESEARCH INSTITUTE OF STATE GRID SHANDONG ELECTRIC POWER COMPANY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411673726.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The uneven electric field distribution problem caused by high dielectric constant fillers in anti-fouling flash coatings, resulting in local electric field distortion and reduced insulation strength.

Method used

By preparing silicon oxide particles with active groups and high dielectric constant fillers, chemical bonding is performed under the action of a catalyst, a chemical bonding layer is formed, and a dielectric gradient structure that is gradually reduced is formed in the coating.

Benefits of technology

The internal structure of the anti-fouling flash coating is uniformized, the dielectric performance difference between high dielectric constant filler and silicone rubber film forming substance is reduced, local electric field distortion is avoided, and the electrical performance and durability of the coating are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505695A_ABST
    Figure CN119505695A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving dielectric constant uniformity of a high dielectric constant filler modified anti-pollution flashover coating, and belongs to the technical field of anti-pollution flashover coatings. The method comprises the following steps: preparing silicon oxide particles with a first active group and a high dielectric constant filler with a second active group, wherein the first active group and the second active group can be chemically bonded under the action of a catalyst; and mixing the silicon oxide particles with the first active group and the high-dielectric-constant filler with the second active group with polydimethylsiloxane, a cross-linking agent, a solvent and a catalyst to prepare the high-dielectric-constant filler modified anti-pollution flashover coating. According to the method, the dielectric property difference between the high-dielectric-constant filler particles and the silicone rubber film forming matter can be reduced, a continuous and uniformly-changed dielectric property structure is formed, local electric field distortion is avoided, and the method is simple and remarkable in effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anti-pollution flashover coatings, and in particular to a method for improving the dielectric gradient uniformity of an anti-pollution flashover coating modified with a high dielectric constant filler. Background Art

[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] The external insulation equipment of the power system operates in the outdoor environment for a long time. Pollution flashover is one of the main fault forms that threaten the safe and stable operation of the power system. The occurrence of pollution flashover is determined by two factors: one is the accumulation of pollutants in the atmospheric environment on the surface of the external insulation; the other is the wetting of the external insulation surface under humid meteorological conditions after the deposition of dirt. In a dry environment, the dirt on the surface of the external insulation still has a high insulation strength, but under climatic conditions such as light rain, snow, fog, frost, and dew, after wetting, the soluble electrolytes and other substances in the dirt layer gradually dissolve in water to form a conductive film, which increases the conductivity of the external insulation surface, thereby causing discharge flashover along the surface of the external insulation, namely pollution flashover. The occurrence of pollution flashover can cause accidents such as line tripping and power outages, seriously endangering the safe operation of the power grid and causing huge economic losses. Therefore, preventing pollution flashover on the surface of the external insulation equipment of the power system is an important task to ensure the safe operation of the power system lines.

[0004] Silicone rubber (RTV) anti-pollution flashover coating has become an effective pollution flashover prevention measure due to its excellent hydrophobicity and hydrophobic migration. However, RTV anti-pollution flashover coating belongs to organic polymer materials, and its aging resistance, flame retardancy, arc resistance and mechanical properties are poor. After 3 to 5 years of operation, it is easy to experience aging, cracking, peeling, electric traces, and electrical erosion, which leads to the decline of insulation protection performance, causing pollution flashover accidents, and seriously threatening the safe operation of the power grid. In order to improve the service performance of RTV anti-pollution flashover coating, nanomaterials are usually added to the system to make it have the characteristics of both organic and inorganic materials, which can greatly improve the performance and service life of RTV anti-pollution flashover coating. For example, patents such as CN109233620B, CN102321434B, and CN116855170B disclose that inorganic fillers such as silicon oxide, red iron oxide, aluminum hydroxide, boron nitride, and titanium dioxide are added to RTV anti-pollution flashover coating as reinforcing agents, flame retardants, and color fillers. However, the introduction of inorganic fillers will form a large number of interface areas between the silicone rubber film-forming material and the filler. Due to the huge difference in dielectric constant between the film-forming material and the inorganic filler, and the poor compatibility between the two due to factors such as filler agglomeration or defects, severe local electric field distortion occurs at the interface between the film-forming material and the inorganic filler, which causes breakdown and reduces the insulation strength of the outer insulating coating. Moreover, the reduction in insulation strength becomes more obvious with the increase in particle type and content.

[0005] Modifying the surface of filler particles by physical and chemical methods is the main way to improve the interface characteristics between the film-forming material and the inorganic filler particles, but this method is only effective for silicon oxide particles (relative dielectric constant: 3.9-4.0) whose dielectric constant is not much different from that of silicone rubber (relative dielectric constant: 2.7-3.3). For filler particles with larger dielectric constants, such as aluminum oxide (relative dielectric constant: 9-10), red iron oxide (relative dielectric constant: 14.2), titanium oxide (relative dielectric constant: 110-120), etc., even after modification by physical and chemical methods, there are still problems such as poor continuity of dielectric gradient and uneven change of electric field gradient.

[0006] Therefore, how to provide a method to improve the dielectric gradient uniformity of high dielectric constant modified anti-pollution flashover coatings and solve the electric field distortion caused by high dielectric constants to prepare anti-pollution flashover coatings with good comprehensive performance is an urgent problem to be solved. Summary of the invention

[0007] In view of this, the present invention provides a method for improving the dielectric gradient uniformity of an anti-pollution flashover coating modified with a high dielectric constant filler, thereby solving the problem of uneven electric field distribution when the anti-pollution flashover coating is modified with a high dielectric constant filler.

[0008] In a first aspect, the present invention provides a method for improving the dielectric gradient uniformity of an anti-fouling flashover coating modified with a high dielectric constant filler, comprising the following steps:

[0009] Prepare silicon oxide particles having a first active group and a high dielectric constant filler having a second active group, wherein the first active group and the second active group can be chemically bonded under the action of a catalyst; the high dielectric constant filler comprises one or more of aluminum oxide, red iron oxide, titanium oxide, magnesium oxide or magnesium hydroxide;

[0010] The anti-fouling flashover coating modified by the high dielectric constant filler is prepared by mixing silicon oxide particles having a first active group and a high dielectric constant filler having a second active group with polydimethylsiloxane, a crosslinking agent, a solvent and a catalyst.

[0011] Preferably, the particle size of the silicon oxide particles is 10 to 100 nm, and the particle size of the high dielectric constant filler is 1 to 10 μm.

[0012] Preferably, the first reactive group and the second reactive group are selected from any of the following functional group combinations:

[0013] a. Epoxy and amino groups;

[0014] b. Epoxy and mercapto groups;

[0015] c. Vinyl and mercapto.

[0016] Furthermore, the preparation method of the silicon oxide particles having the first active group is: reacting the silicon oxide particles with a silane coupling agent having an epoxy group, an amino group, a vinyl group or a mercapto group;

[0017] The preparation method of the high dielectric constant filler with the second active group is: reacting the high dielectric constant filler with a silane coupling agent having an epoxy group, an amino group, a vinyl group or a mercapto group.

[0018] Preferably, the crosslinking agent is selected from one or more of methyltributylacetoximate silane, phenyltributylacetoximate silane or tetrabutylketoxime silane.

[0019] Preferably, the solvent is selected from one or more of toluene, xylene, ethyl acetate, butyl acetate or acetone.

[0020] Preferably, the catalyst is selected from one or more of acetic acid, oxalic acid or propionic acid.

[0021] Preferably, the mass ratio of the silicon oxide particles having the first active group, the high dielectric constant filler having the second active group, polydimethylsiloxane, the crosslinking agent, the solvent and the catalyst is (5-10):(5-10):(70-75):(0.5-1):(10-20):(0.5-2).

[0022] Preferably, the specific method for preparing the anti-pollution flashover coating modified with a high dielectric constant filler comprises the following steps:

[0023] Adding silicon oxide particles having a first active group and a high dielectric constant filler having a second active group into a solvent, stirring and dispersing the particles to obtain a particle dispersion;

[0024] Adding the particle dispersion into polydimethylsiloxane, then adding a crosslinking agent, and stirring evenly to obtain a mixed slurry;

[0025] A catalyst is added to the mixed slurry, and the mixture is poured after being stirred evenly. After solidification, an anti-fouling flashover coating modified with a high dielectric constant filler is obtained.

[0026] In a second aspect, the present invention provides an anti-pollution flashover coating modified with a high dielectric constant filler prepared by the above method.

[0027] Compared with the prior art, the present invention has achieved the following beneficial effects:

[0028] (1) The present invention utilizes chemical bonding between the active groups of the high dielectric constant filler and the active groups of the silicon oxide particles, and utilizes chemical bonding to achieve chemical bonding between the high dielectric constant particles and the silicon oxide particles, thereby forming a complete chemical bonding layer, avoiding the generation of phase interface defects within the coating, and improving the homogeneity of the internal structure of the anti-fouling flashover coating.

[0029] (2) In the present invention, the silicon oxide particles are wrapped on the surface of the high dielectric constant filler by chemical bonding, which effectively realizes the step-by-step reduction of the dielectric gradient of the high dielectric constant filler, the silicon oxide particles, and the silicone rubber matrix. After the multi-level dielectric gradient changes, the dielectric property difference between the high dielectric constant filler particles and the silicone rubber film-forming material is reduced, forming a continuous and uniformly changing dielectric gradient structure, realizing the regulation of the electric field distribution of the anti-fouling flashover coating, and avoiding the local electric field distortion caused by the sudden change of the dielectric properties in the interface area between the filler particles and the silicone rubber film-forming material.

[0030] (3) The construction of the dielectric gradient structure of the anti-fouling flashover coating in the present invention is based on chemical bonding self-assembly technology, which does not require lamination and external electric field, magnetic field and other forces. The method is simple and convenient, the effect is significant, and it has universal applicability. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0032] Figure 1 is a diagram of the compatibility test results of Example 1 of the present invention;

[0033] Figure 2 is a schematic diagram of the chemical bonding self-assembly process of Example 1 and Example 2 of the present invention;

[0034] Figure 3 Schematic diagram of the dielectric gradient structure of the coating formed in Example 1 and Example 2 of the present invention;

[0035] Figure 4 is a compatibility test result diagram of Comparative Example 2 of the present invention;

[0036] Figure 5 It is a compatibility test result diagram of Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0037] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0038] Explanation of terms

[0039] Dielectric constant and relative dielectric constant: Dielectric constant is the main parameter that reflects the dielectric properties or polarization properties of piezoelectric material dielectrics under the action of electrostatic fields, and is usually represented by ε. It indicates that when an external electric field is applied, the dielectric will generate induced charges and weaken the electric field. The ratio of the original external electric field (in a vacuum) to the electric field in the dielectric is the relative dielectric constant (or relative permittivity), also known as dielectric constant, which is related to frequency. The dielectric constant is the product of the relative dielectric constant and the absolute dielectric constant in a vacuum. If a material with a high dielectric constant is placed in an electric field, the intensity of the electric field will drop significantly in the dielectric. Generally, substances with a relative dielectric constant greater than 3.6 are polar substances; substances with a relative dielectric constant in the range of 2.8 to 3.6 are weakly polar substances; and substances with a relative dielectric constant less than 2.8 are non-polar substances. In the present invention, fillers with a relative dielectric constant higher than 5.0 are referred to as high dielectric constant fillers.

[0040] As described in the background technology, the existing anti-pollution flashover coating modified with high dielectric constant fillers has problems such as poor dielectric gradient continuity and uneven electric field gradient change. Therefore, the present invention provides a method for improving the uniformity of dielectric gradient of the anti-pollution flashover coating modified with high dielectric constant fillers, comprising the following steps:

[0041] Prepare silicon oxide particles having a first active group and a high dielectric constant filler having a second active group, wherein the first active group and the second active group can be chemically bonded under the action of a catalyst;

[0042] The high dielectric constant filler includes one or more of aluminum oxide, red iron oxide, titanium oxide, magnesium oxide or magnesium hydroxide;

[0043] The anti-fouling flashover coating modified by the high dielectric constant filler is prepared by mixing silicon oxide particles having a first active group and a high dielectric constant filler having a second active group with polydimethylsiloxane, a crosslinking agent, a solvent and a catalyst.

[0044] In the present invention, since the high dielectric constant filler particles have greater polarity and more modified functional groups on the surface, they will react with more silicon oxide particles to form a coating structure. The present invention uses silicon oxide particles with a dielectric constant between the dielectric constant of silicone rubber and the high dielectric constant filler as the transition section of the dielectric gradient, and the silicon oxide particles are wrapped on the surface of the high dielectric constant filler through chemical bonding, effectively realizing the step-by-step reduction of the dielectric gradient of the high dielectric constant filler, silicon oxide particles, and silicone rubber matrix. After the change of the multi-level dielectric gradient, the dielectric property difference between the high dielectric constant filler particles and the silicone rubber film-forming material is reduced, forming a continuous and uniformly changing dielectric gradient structure, realizing the regulation of the electric field distribution of the anti-fouling flashover coating, avoiding the local electric field distortion caused by the sudden change of the dielectric property of the interface area between the filler particles and the silicone rubber film-forming material, and improving the electrical performance of the coating.

[0045] At the same time, under the chemical bonding action of the active groups, a complete chemical bonding layer is formed at the particle-particle interface, which enhances the compatibility between the particle-particle interface and the particle-silicone rubber interface, thereby avoiding the generation of phase interface defects within the coating, improving the uniformity of the coating, and increasing the durability and stability of the coating.

[0046] The particle size of the silicon oxide particles of the present invention is 10-100 nm, and the particle size of the high dielectric constant filler is 1-10 μm. The particle size mainly affects the steric hindrance. The small-sized silicon oxide particles are selected mainly to reduce the steric hindrance so that more silicon oxide particles can react with the particles of the high dielectric constant filler.

[0047] In the present invention, the first reactive group and the second reactive group are selected from any of the following functional group combinations:

[0048] a. Epoxy and amino groups;

[0049] b. Epoxy and mercapto groups;

[0050] c. Vinyl and mercapto.

[0051] The present invention does not impose any special restriction on the order of selecting the first reactive group and the second reactive group in the above-listed combinations. For example, the first reactive group may be an epoxy group and the second reactive group may be an amino group, or the first reactive group may be an amino group and the second reactive group may be an epoxy group.

[0052] It is also understood that the active group that can be chemically bonded can also be selected from any combination of isocyanate group and hydroxyl group, amino group or carboxyl group. The above combinations can all be chemically bonded at room temperature under the action of a catalyst. In view of the ease of modification, the present invention preferably uses a functional group combination of epoxy group and amino group or thiol group and vinyl group and thiol group.

[0053] In the present invention, the preparation method of the silicon oxide particles having the first active group is: reacting the silicon oxide particles with a silane coupling agent having an epoxy group, an amino group, a vinyl group or a mercapto group;

[0054] The preparation method of the high dielectric constant filler with the second active group is: reacting the high dielectric constant filler with a silane coupling agent having an epoxy group, an amino group, a vinyl group or a mercapto group.

[0055] The present invention does not impose any special restrictions on the reaction process of the above-mentioned silicon oxide particles or high dielectric constant fillers and silane coupling agents, and those skilled in the art can achieve the above-mentioned reaction according to conventional means in the art. The reaction process mainly includes the dispersion of silicon oxide particles or high dielectric constant fillers, the hydrolysis of silane coupling agents, and the reaction of silicon oxide particles or high dielectric constant fillers with silane coupling agent hydrolyzate.

[0056] In one or more embodiments of the present invention, the preparation method of the silicon oxide particles having the first active group and the high dielectric constant filler having the second active group is: disperse the silicon oxide particles or the high dielectric constant filler in a solvent (water and / or ethanol), disperse by ultrasound and shearing, add the silane coupling agent hydrolyzate under stirring at 60 to 90°C, react for 10 to 30 hours, centrifuge and wash, and then dry for standby use. The present invention does not impose any special restrictions on the preparation process of the silane coupling agent hydrolyzate, and the preparation method commonly used in the art can be used, for example, ultrasonic dispersion in water can be used, or hydrolysis under acidic conditions can be used. Those skilled in the art can choose as needed according to actual conditions.

[0057] In the present invention, the silane coupling agent with an epoxy group includes but is not limited to γ-(2,3-epoxypropyloxy)propyltrimethoxysilane (KH-560), γ-glycidyloxypropyltriethoxysilane (KH-561), 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane (KH-1770), 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane (KH-1771), 3-(2,3-epoxypropyloxy)propylmethyldimethoxysilane (KH-781), etc.

[0058] In the present invention, the silane coupling agent with an amino group includes but is not limited to γ-aminopropyltriethoxysilane (KH-550), γ-aminopropyltrimethoxysilane (KH-540), γ-aminopropylsilanetriol (KH-553), N-2-aminoethyl-3-aminopropylmethyldimethoxysilane, N-2-aminoethyl-3-aminopropyltrimethoxysilane, N-2-aminoethyl-3-aminopropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, etc.

[0059] In the present invention, the silane coupling agent with a mercapto group includes, but is not limited to, 3-mercaptopropyltrimethoxysilane (KH-591), γ-mercaptopropyltriethoxysilane (KH-592), 3-mercaptopropylmethyldimethoxysilane, and the like.

[0060] In the present invention, the silane coupling agent with a vinyl group includes but is not limited to vinyl trichlorosilane, vinyl trimethoxysilane, vinyl triethoxysilane and the like.

[0061] In the present invention, the crosslinking agent is selected from one or more of methyltributylacetoximosilane, phenyltributylacetoximosilane or tetrabutylketoximesilane. The crosslinking agent can promote the curing and crosslinking of the silicone rubber film-forming material polydimethoxysilane.

[0062] In the present invention, the solvent is selected from one or more of toluene, xylene, ethyl acetate, butyl acetate or acetone. The main function of the solvent is to dilute and disperse, so that the various substances can be better mixed and the uniformity of the coating is improved.

[0063] In the present invention, the catalyst is selected from one or more of acetic acid, oxalic acid or propionic acid, and the acidic conditions provided by the catalyst can promote the occurrence of the chemical bonding reaction between the first active group and the second active group. In principle, other acids can also be selected as long as they can promote the chemical bonding reaction.

[0064] In the present invention, the mass ratio of the silicon oxide particles having the first active group, the high dielectric constant filler having the second active group, the polydimethylsiloxane, the crosslinking agent, the solvent and the catalyst is (5-10): (5-10): (70-75): (0.5-1): (10-20): (0.5-2). It is understood that those skilled in the art may also add other additives that are beneficial to the preparation or application performance of the coating, such as defoaming agents, flame retardants, hydrophobic agents and other additives, and the present invention does not impose any special restrictions on this.

[0065] In the present invention, the specific method for preparing the anti-pollution flashover coating modified with a high dielectric constant filler comprises the following steps:

[0066] Adding silicon oxide particles having a first active group and a high dielectric constant filler having a second active group into a solvent, stirring and dispersing the particles to obtain a particle dispersion;

[0067] Adding the particle dispersion into polydimethylsiloxane, then adding a crosslinking agent, stirring evenly to obtain a mixed slurry (component A);

[0068] A catalyst (component B) is added to the mixed slurry, and the mixture is evenly stirred and then poured. After curing, an anti-fouling flashover coating modified with a high dielectric constant filler is obtained.

[0069] The present invention does not impose any particular limitation on the specific methods of stirring, dispersing and solidifying, and any commonly used method in the art may be used.

[0070] The present invention can prepare the high dielectric constant filler modified anti-pollution flashover coating according to the following formula:

[0071] Component A:

[0072] 5 to 10 parts of silicon oxide particles having a first active group,

[0073] 5 to 10 parts of a high dielectric constant filler having a second active group,

[0074] 70-75 parts of polydimethylsiloxane,

[0075] Cross-linking agent 0.5-1 part,

[0076] 10-20 parts of solvent;

[0077] Component B: catalyst;

[0078] The mass ratio of component A to component B is 100:(0.5-2).

[0079] When preparing the coating, component A and component B are mixed, and then poured to obtain the anti-fouling flashover coating modified with a high dielectric constant filler.

[0080] The present invention also provides an anti-pollution flashover coating modified with a high dielectric constant filler prepared by the above method. The anti-pollution flashover coating modified with a high dielectric constant filler provided by the present invention can improve the comprehensive performance of the anti-pollution flashover coating while still maintaining a relative dielectric constant below 4.0, good insulation performance and dielectric uniformity, and dielectric strength can be maintained above 20kV / mm.

[0081] The technical solution of the present invention is further described below in conjunction with specific embodiments. The present invention has no special restrictions on the sources of the following reagents, and commercial products well known to those skilled in the art can be used.

[0082] Example 1

[0083] This embodiment provides a method for preparing an anti-pollution flashover coating modified with a high dielectric constant filler.

[0084] (1) Preparation of epoxy-modified silicon oxide particles:

[0085] ① Disperse silicon oxide particles (average particle size of 20 nm) into an ethanol solution at a mass ratio of 1:20, stir under magnetic stirring for 5 min, then shear disperse at a speed of 1000 r / min for 10 min, transfer to ultrasonic wave, and ultrasonically disperse at a power of 1 kW for 10 min to obtain a particle dispersion;

[0086] ② Prepare a silane coupling agent hydrolyzate, specifically: weigh γ-glycidyloxypropyltrimethoxysilane (KH-560) according to 20% of the mass of silicon oxide and add it to deionized water, stir and disperse it evenly, and then adjust the pH to 4.0-5.0 to obtain a silane coupling agent hydrolyzate;

[0087] ③ Transfer the particle dispersion in step ① to an 80°C oil bath, and add the silane coupling agent hydrolyzate in step ② drop by drop under constant stirring. After the addition is complete, continue stirring and reacting for 24 hours;

[0088] ④ After washing the modified silicon oxide particles three times by centrifugation with ethanol, transfer them to a 60°C oven for drying.

[0089] (2) Preparation of amino-modified alumina:

[0090] ① Disperse alumina particles (average particle size of 2 μm) into an ethanol solution at a mass ratio of 1:30, stir under magnetic stirring for 5 min, then shear disperse at a speed of 1000 r / min for 10 min, transfer to ultrasonic wave, and ultrasonically disperse at a power of 1 kW for 10 min to obtain a particle dispersion;

[0091] ② Prepare a silane coupling agent hydrolyzate, specifically: weigh γ-aminopropyltriethoxysilane (KH-550) according to 30% of the mass of alumina, add it to deionized water, stir and disperse it evenly, and adjust the pH to 4.0-5.0 to obtain a silane coupling agent hydrolyzate;

[0092] ③ Transfer the particle dispersion in step ① to an 80°C oil bath, and add the silane coupling agent hydrolyzate in step ② drop by drop under constant stirring. After the addition is complete, continue stirring and reacting for 24 hours;

[0093] ④ After washing the modified alumina particles by centrifugation for 3 times with ethanol, transfer them to a 60°C oven for drying for later use.

[0094] (3) Anti-pollution flashover coating formula (the following parts are all by mass):

[0095] Component A:

[0096] Polydimethylsiloxane: 70 parts;

[0097] Xylene: 14 parts;

[0098] Epoxy-modified silicon oxide particles: 10 parts;

[0099] Amino-modified alumina: 5 parts;

[0100] Methyl tributylidene oxime silane: 1 part;

[0101] Component B is acetic acid.

[0102] (4) Preparation of anti-fouling flashover coating:

[0103] ① Add epoxy-modified silicon oxide particles and amino-modified aluminum oxide into xylene, stir evenly, shear for 20 minutes, and ultrasonically disperse for 10 minutes to obtain a particle dispersion;

[0104] ② Add the particle dispersion into polydimethylsiloxane and methyl tributylidene oxime silane, and stir and disperse them evenly in a vacuum reactor at a speed of 500 r / min;

[0105] ③According to the mass ratio of component A to component B of 100:1, acetic acid was added to component A, stirred evenly, poured into a mold, and cured at room temperature for 72 hours to obtain a sample.

[0106] Example 2

[0107] This embodiment provides a method for preparing an anti-pollution flashover coating modified with a high dielectric constant filler.

[0108] (1) Preparation of epoxy-modified silicon oxide particles:

[0109] ① Disperse silicon oxide particles (average particle size of 50 nm) into an ethanol solution at a mass ratio of 1:20, stir under magnetic stirring for 5 min, then shear disperse at a speed of 1000 r / min for 10 min, transfer to ultrasonic wave, and ultrasonically disperse at a power of 1 kW for 10 min to obtain a particle dispersion;

[0110] ② Prepare a silane coupling agent hydrolyzate, specifically: weigh γ-glycidyloxypropyltrimethoxysilane (KH-560) according to 20% of the mass of silicon oxide, add it to deionized water, stir and disperse it evenly, and adjust the pH to 4.0-5.0 to obtain a silane coupling agent hydrolyzate;

[0111] ③ Transfer the particle dispersion in step ① to an 80°C oil bath, and add the silane coupling agent hydrolyzate in step ② drop by drop under constant stirring. After the addition is complete, continue stirring and reacting for 24 hours;

[0112] ④ After washing the modified silicon oxide particles three times by centrifugation with ethanol, transfer them to a 60°C oven for drying.

[0113] (2) Preparation of mercapto-modified titanium oxide:

[0114] ① Disperse titanium oxide particles (average particle size of 10 μm) into an ethanol solution at a mass ratio of 1:30, stir under magnetic stirring for 5 min, then shear disperse at a speed of 1000 r / min for 10 min, transfer to ultrasonic wave, and ultrasonically disperse at a power of 1 kW for 10 min to obtain a particle dispersion;

[0115] ② Prepare a silane coupling agent hydrolyzate, specifically: weigh γ-mercaptopropyltrimethoxysilane (KH-591) according to 25% of the mass of titanium oxide and add it to deionized water, stir and disperse it evenly, and adjust the pH to 4.0-5.0 to obtain a silane coupling agent hydrolyzate;

[0116] ③ Transfer the particle dispersion in step ① to an 80°C oil bath, and add the silane coupling agent hydrolyzate in step ② drop by drop under constant stirring. After the addition is complete, continue stirring and reacting for 24 hours;

[0117] ④ After washing the modified alumina particles by centrifugation for 3 times with ethanol, transfer them to a 60°C oven for drying for later use.

[0118] (3) Anti-pollution flashover coating formula (the following parts are all by mass):

[0119] Component A:

[0120] Polydimethylsiloxane: 75 parts;

[0121] Toluene: 10 parts;

[0122] Epoxy-modified silicon oxide particles: 8 parts;

[0123] Mercapto-modified alumina: 6 parts;

[0124] Methyl tributylidene oxime silane: 1 part;

[0125] Component B is acetic acid.

[0126] (4) Preparation of anti-fouling flashover coating:

[0127] ① Add epoxy-modified silicon oxide particles and mercapto-modified aluminum oxide to toluene, stir evenly, shear for 20 minutes, and ultrasonically disperse for 10 minutes to obtain a particle dispersion;

[0128] ② Add the particle dispersion into polydimethylsiloxane and methyl tributylidene oxime silane, and stir and disperse them evenly in a vacuum reactor at a speed of 500 r / min;

[0129] ③According to the mass ratio of component A to component B of 100:1, acetic acid was added to component A, stirred evenly, poured into a mold, and cured at room temperature for 72 hours to obtain a sample.

[0130] Comparative Example 1

[0131] Compared with Example 1, this comparative example does not add epoxy-modified silicon oxide particles and amino-modified aluminum oxide.

[0132] (1) The formula of anti-pollution flashover coating (the following parts are all by mass) is as follows:

[0133] Component A:

[0134] Polydimethylsiloxane: 70 parts;

[0135] Xylene: 14 parts;

[0136] Methyl tributylidene oxime silane: 1 part;

[0137] Component B is acetic acid.

[0138] (2) Preparation of anti-fouling flashover coating:

[0139] ① Add xylene to polydimethylsiloxane and methyl tributylidene oxime silane, and stir and disperse them evenly in a vacuum reactor at a speed of 500r / min;

[0140] ②According to the mass ratio of component A to component B of 100:1, acetic acid was added to component A, stirred evenly, poured into a mold, and cured at room temperature for 72 hours to obtain a sample.

[0141] Comparative Example 2

[0142] The difference between this comparative example and Example 1 is that this comparative example does not contain epoxy-modified silicon oxide particles.

[0143] (1) Anti-pollution flashover coating formula (the following parts are all by mass):

[0144] Component A:

[0145] Polydimethylsiloxane: 70 parts;

[0146] Xylene: 14 parts;

[0147] Amino-modified alumina: 5 parts;

[0148] Methyl tributylidene oxime silane: 1 part;

[0149] Component B is acetic acid.

[0150] (2) Preparation of anti-fouling flashover coating:

[0151] ① Add amino-modified alumina to xylene, stir evenly, shear for 20 minutes, and ultrasonically disperse for 10 minutes to obtain a particle dispersion;

[0152] ② Add the particle dispersion into polydimethylsiloxane and methyl tributylidene oxime silane, and stir and disperse them evenly in a vacuum reactor at a speed of 500 r / min;

[0153] ③According to the mass ratio of component A to component B of 100:1, acetic acid was added to component A, stirred evenly, poured into a mold, and cured at room temperature for 72 hours to obtain a sample.

[0154] Comparative Example 3

[0155] The difference between this comparative example and Example 1 is that the silicon oxide and aluminum oxide are not modified in this comparative example, and an epoxy silane coupling agent (KH-560) is added to the coating formula as an additive.

[0156] (1) Anti-pollution flashover coating formula (the following parts are all by mass):

[0157] Component A:

[0158] Polydimethylsiloxane: 70 parts;

[0159] Xylene: 14 parts;

[0160] Silicon oxide particles (20 nm): 10 parts;

[0161] Alumina (2 μm): 5 parts;

[0162] KH-560: 2 parts;

[0163] Methyl tributylidene oxime silane: 1 part;

[0164] Component B is acetic acid.

[0165] (2) Preparation of anti-fouling flashover coating:

[0166] ① Add silicon oxide particles and aluminum oxide to xylene, then add KH-560, stir evenly, shear for 20 minutes, and ultrasonically disperse for 10 minutes to obtain a particle dispersion;

[0167] ② Add the particle dispersion into polydimethylsiloxane and methyl tributylidene oxime silane, and stir and disperse them evenly in a vacuum reactor at a speed of 500 r / min;

[0168] ③According to the mass ratio of component A to component B of 100:1, acetic acid was added to component A, stirred evenly, poured into a mold, and a sample was obtained after curing.

[0169] Comparative Example 4

[0170] The difference between this comparative example and Example 1 is that the epoxy-modified silica particles are replaced by amino-modified silica particles (ie, the modification methods of silica and alumina are the same), and the other steps and formulas are the same as those in Example 1.

[0171] The preparation method of the amino-modified silicon oxide particles in this comparative example is as follows:

[0172] ① Disperse silicon oxide particles (average particle size of 20 nm) into an ethanol solution at a mass ratio of 1:20, stir under magnetic stirring for 5 min, then shear disperse at a speed of 1000 r / min for 10 min, transfer to ultrasonic wave, and ultrasonically disperse at a power of 1 kW for 10 min to obtain a particle dispersion;

[0173] ② Prepare a silane coupling agent hydrolyzate, specifically: weigh γ-aminopropyl triethoxysilane (KH-550) according to 20% of the mass of silicon oxide, add it to deionized water, stir and disperse it evenly, and adjust the pH to 4.0-5.0 to obtain a silane coupling agent hydrolyzate;

[0174] ③ Transfer the particle dispersion in step ① to an 80°C oil bath, and add the silane coupling agent hydrolyzate in step ② drop by drop under constant stirring. After the addition is complete, continue stirring and reacting for 24 hours;

[0175] ④ After washing the modified silicon oxide particles three times by centrifugation with ethanol, transfer them to a 60°C oven for drying.

[0176] Comparative Example 5

[0177] The difference between this comparative example and Example 1 is that the aluminum oxide particles in this comparative example are nano aluminum oxide particles with an average particle size of 20 nm, and the rest are the same as Example 1.

[0178] Comparative Example 6

[0179] The difference between this comparative example and Example 1 is that the anti-fouling flashover coating formula of this comparative example does not contain component B (ie, no acetic acid is added), and the rest is the same as Example 1.

[0180] Test example

[0181] The anti-fouling flashover coatings of Examples 1 to 2 and Comparative Examples 1 to 6 are tested for appearance, compatibility, electrical properties, and resistance to ultraviolet aging. The compatibility is determined by a sedimentation test of the coating. After the prepared component A coating is left standing at room temperature for 24 hours, the compatibility is judged by whether the coating is stratified internally. The aging resistance is evaluated by exposure cycles (30 cycles) according to the method specified in GB / T16422.3-2022 Plastics Laboratory Light Source Exposure Test Method Part 3: Fluorescent Ultraviolet Lamp Standard. After the evaluation, the results are evaluated according to the GB / T1766-2008 Paint and Varnish. Coating Aging Rating Method. The test results are shown in Table 1.

[0182] Table 1 Performance measurement of anti-pollution flashover coatings of Examples 1 to 2 and Comparative Examples 1 to 6

[0183]

[0184] The addition of modified filler particles in Example 1 and Example 2 greatly improves the compatibility of the filler particles and the organic film-forming material in the anti-fouling flashover coating ( Figure 1 The compatibility test result of Example 1 is shown in Figure 1), which improves the aging resistance of the anti-fouling flashover coating, and the aging grade is increased from Grade 2 in Comparative Example 1 to Grade 0. At the same time, under the action of chemical bonding self-assembly, a dielectric gradient structure is formed inside the coating, which avoids local distortion of the electric field, so that the electrical insulation performance is maintained. The schematic diagram of the chemical bonding self-assembly process is shown in Figure 1. Figure 2 As shown, the schematic diagram of the dielectric gradient structure of the formed coating is as follows Figure 3 As shown. Comparative Example 1 has excellent electrical insulation performance because no filler particles are added, but the aging resistance is poor. In Comparative Examples 2 and 4, modified silicon oxide and aluminum oxide are added. Due to the high density of aluminum oxide, it settles significantly in the coating, resulting in general compatibility within the coating. The compatibility test diagram of Comparative Example 2 is shown in FIG. Figure 4 In Comparative Example 3, the silicon oxide and aluminum oxide particles were not modified, and there was an obvious interface between the inorganic filler particles and the organic film-forming system, such as Figure 5As shown, the compatibility is poor, resulting in obvious stratification of the coating after standing, and a significant decrease in electrical performance. In Comparative Example 5, because the particle sizes of silicon oxide and aluminum oxide are the same, although chemical bonding can occur between the two, due to steric hindrance, silicon oxide cannot form a coating on the surface of aluminum oxide, resulting in direct contact between aluminum oxide with a high dielectric constant and the film-forming material, resulting in electric field distortion inside the coating and a decrease in electrical performance. In Comparative Example 6, due to the lack of an acidic catalyst, the active groups between silicon oxide and aluminum oxide cannot undergo chemical bonding to form a dielectric gradient structure, resulting in a decrease in electrical insulation.

[0185] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for improving the dielectric gradient uniformity of an anti-fouling flashover coating modified with a high dielectric constant filler, characterized in that: The steps include: Prepare silicon oxide particles having a first active group and a high dielectric constant filler having a second active group, wherein the first active group and the second active group can be chemically bonded under the action of a catalyst; the high dielectric constant filler comprises one or more of aluminum oxide, red iron oxide, titanium oxide, magnesium oxide or magnesium hydroxide; The anti-fouling flashover coating modified by the high dielectric constant filler is prepared by mixing silicon oxide particles having a first active group and a high dielectric constant filler having a second active group with polydimethylsiloxane, a crosslinking agent, a solvent and a catalyst.

2. The method according to claim 1, characterized in that The particle size of the silicon oxide particles is 10 to 100 nm, and the particle size of the high dielectric constant filler is 1 to 10 μm.

3. The method according to claim 1, characterized in that The first reactive group and the second reactive group are selected from any of the following functional group combinations: a. Epoxy and amino groups; b. Epoxy and mercapto groups; c. Vinyl and mercapto.

4. The method according to claim 3, characterized in that The method for preparing the silicon oxide particles having the first active group is: reacting the silicon oxide particles with a silane coupling agent having an epoxy group, an amino group, a vinyl group or a mercapto group; The preparation method of the high dielectric constant filler with the second active group is: reacting the high dielectric constant filler with a silane coupling agent having an epoxy group, an amino group, a vinyl group or a mercapto group.

5. The method according to claim 1, characterized in that The crosslinking agent is selected from one or more of methyltributylacetoximosilane, phenyltributylacetoximosilane or tetrabutylketoximesilane.

6. The method according to claim 1, characterized in that The solvent is selected from one or more of toluene, xylene, ethyl acetate, butyl acetate or acetone.

7. The method according to claim 1, characterized in that The catalyst is selected from one or more of acetic acid, oxalic acid or propionic acid.

8. The method according to claim 1, characterized in that The mass ratio of the silicon oxide particles having the first active group, the high dielectric constant filler having the second active group, polydimethylsiloxane, the crosslinking agent, the solvent and the catalyst is (5-10):(5-10):(70-75):(0.5-1):(10-20):(0.5-2).

9. The method according to claim 1, characterized in that The specific method for preparing the anti-pollution flashover coating modified with a high dielectric constant filler comprises the following steps: Adding silicon oxide particles having a first active group and a high dielectric constant filler having a second active group into a solvent, stirring and dispersing the particles to obtain a particle dispersion; Adding the particle dispersion into polydimethylsiloxane, then adding a crosslinking agent, and stirring evenly to obtain a mixed slurry; A catalyst is added to the mixed slurry, and the mixture is poured after being stirred evenly. After solidification, an anti-fouling flashover coating modified with a high dielectric constant filler is obtained.

10. An anti-fouling flashover coating modified with a high dielectric constant filler prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • RTV (room temperature vulcanized silicone rubber) anti-pollution flashover paint and preparation method thereof

    CN102321434B

  • A solvent-free RTV anti-flashover coating and its preparation method

    CN109233620B

  • A kind of RTV anti-pollution flashover coating and preparation method

    CN116855170B

  • High-dielectric photosensitive resin-based composite material as well as preparation method and application thereof

    CN111100425A

  • Prepreg and circuit board

    CN111909476A